2019
DOI: 10.3389/fpls.2019.01292
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ghAlba_4 and ghAlba_5 Proteins in Cotton Inhibits Root Growth and Increases Sensitivity to Drought and Salt Stresses

Abstract: We found 33, 17, and 20 Alba genes in Gossypium hirsutum, Gossypium arboretum, and Gossypium raimondii, respectively. The Alba protein lengths ranged from 62 to 312 aa, the molecular weight (MW) from 7.003 to 34.55 kDa, grand average hydropathy values of −1.012 to 0.609 and isoelectric (pI) values of −3 to 11. Moreover, miRNAs such as gra-miR8770 targeted four genes, gra-miR8752 and gra-miR8666 targeted three genes, and each and gra-miR8657 a, b, c, d, e targeted 10 genes each, while the rests targeted 1 to 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 96 publications
(110 reference statements)
5
20
0
Order By: Relevance
“…Similarly, Trypanosoma brucei ALBAs were detected in association with mRNAs, exclusively in cytoplasmic stress granules following nutrient stress [ 7 , 8 ]. In plants, ALBA proteins have also been connected to various stress responses [ 10 , 14 , 15 ]. In rice seedlings, significant changes in the relative expression of ALBA genes were demonstrated following various abiotic stress and phytohormone treatments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Trypanosoma brucei ALBAs were detected in association with mRNAs, exclusively in cytoplasmic stress granules following nutrient stress [ 7 , 8 ]. In plants, ALBA proteins have also been connected to various stress responses [ 10 , 14 , 15 ]. In rice seedlings, significant changes in the relative expression of ALBA genes were demonstrated following various abiotic stress and phytohormone treatments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, differential expression upon abiotic stress application (water and salt stress) was observed for ALBA genes in Gossypium hirsutum (cotton) leaves, roots, and stems. In leaves and roots, two genes GhALBA_4 and GhALBA_5 were significantly upregulated [ 14 ]. Transgenic plants with reduced expression of these genes were shown to be more sensitive to drought and salt stress [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since high ROS concentrations impaired cell membrane stability (Mittler, 2002(Mittler, , 2006Magwanga et al, 2019) and directly influenced seed vigor, we subsequently investigated seed vigor in the tested genotypes under salt application conditions. From the seed staining results on ½MS medium, it was observed that seed vigor was comparable among different genotypes, and the exogenous salt treatment decreased seed vigor among all of the tested genotypes (Fig.…”
Section: Abi4-rbohd/vtc2 Module Decreases Cell Membrane Integrity Andmentioning
confidence: 99%
“…Mild heat stress (37 •C) altered the expression of most Arabidopsis Alba genes in in orescences (Náprstková et al, 2021). In cotton (Gossypium hirsutum), GhALBA4 and GhALBA5 were signi cantly induced by water de cit and salinity treatment, and plants in which the expression of these genes was repressed by virus-induced gene silencing (VIGS) were highly sensitive to dehydration as well as salt stress, pointing to their putative roles in abiotic stress tolerance (Magwanga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%